Fabrication of New Nanocomposites (PMMA-SPO-PS-TiC) and Studying Their Structural and Electrical Properties for Humidity Sensors - Bahaa Hussien Rabee; Idrees Oreibi (Institute of Advanced Engineering and Science, 2018)
Samples have been prepared by adding Titanium carbide nanoparticles to the Poly (methyl methacrylate) and Ethylene-alpha olefin co-polymer (SPO) and Polystyrene (PS) with different weight percentages (o, 2, 4, 6 and 8) wt%. The FTIR analysis, electrical, dielectric, and structural properties have been studied.The dielectric loss and The dielectric constant decrease with increasing of Titanium carbide (TiC) nanoparticles. The A.C electrical conductivity increases with increasing of Titanium carbide (TiC) concentrations and frequency. The D.C electrical conductivity increases with increasing of Titanium carbide (TiC) concentration and temperature. The Activation energy decreases with increasing of Titanium carbide (TiC) nanoparticles. The Humidity sensor application showed that the electrical resistance of (PMMA-SPO-PS-TiC) nanocomposites decreases with increase the Humidity.